Geographic Concerns on Flood Climate and Flood Hydrology in Monsoon-Dominated Damodar River Basin, Eastern India. (22nd January 2015) - Ghosh, Sandipan; Mistri, Biswaranjan
Abstract : In the Lower Gangetic Plain of West Bengal, the furious monsoon flood of Damodar River is a recurrent hydrometeorological phenomenon which is now intensified by the human activities. At present, the flood regulation system of Damodar Valley Corporation (DVC) is not capable of managing gigantic inflow water (which appeared as surface runoff and channel flow) coming from the wide fan-shaped upper catchment of Damodar River. As a result, the lower basin of Damodar (covering Barddhaman, Hooghly, and Howrah districts of West Bengal) annually experiences low to high magnitude of floods and overflow condition because the existing canal system, streams, palaeochannels, and Damodar River itself have lost their former carrying capacity to accommodate all excess water within its active domain due to over siltation and drainage congestion. So when the DVC dams are not able to regulate flood flow, then extreme rainfall of prolonged duration over the basin turns the normal situation into devastating flood, like the years of 1978 and 2000 in West Bengal. Identifying the existing problems of lower Damodar River, this paper principally tries to assess the potentiality of flood climate and to estimate the contributing rainfall-runoff, peak discharge, and existing carrying capacity of river in relation to increasing flood risk of lower basin using the quantitative hydrologic expressions.